Abu Dhabi International Petroleum Exhibition and Conference 2014
DOI: 10.2118/171682-ms
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Mechanical Aspects of Wellbore Stability in Shale Formations: A Literature Review

Abstract: Drilling a shale formation with no borehole problems can be a challenging task. With high content of clays, shale formations are prone to swelling, dispersion, tight hole and other problems. Those problems are well-documented in literature. Different types of clays give different types of problems. For example, when it is exposed to water, a shale sample with a high percentage of smectite tends to swell while another shale sample with a high percentage of kaolinite tends to disintegrate and disperse. The mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…The OBM and SBM have higher operational efficiencies as compared to the WBM. However, the use of OBM and SBM has been declined due to the environmental issues [4][5][6]. This remains WBMs as the preferred ones over the other two types despite their limitations.…”
Section: Introductionmentioning
confidence: 99%
“…The OBM and SBM have higher operational efficiencies as compared to the WBM. However, the use of OBM and SBM has been declined due to the environmental issues [4][5][6]. This remains WBMs as the preferred ones over the other two types despite their limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the use of produced waters with high Na + will result in enhanced swelling, while a high background K + or addition of KCl to reinjected water may aid in inhibiting swelling. Crystalline swelling, This stepwise process is caused by the hydration of the exchangeable cations of the clay (with lower water content) resulting in adsorption of multiple discrete layers of water on the clay surfaces. , Negatively charged clay layers are held together by the interlayer cations that hydrate upon interaction with the polar water molecules, rearranging such that spacing is increased between the clay layers. , This interlayer spacing is dependent on the thermodynamic potential that is constrained by the pH, temperature, and pressure Dispersion, Dispersion is a rapid process in which individual layers of the clay mineral are separated and dispersed in solution with no interactions between the layers. , Hydration of clay minerals causes the pore pressure to be greater than the strength of the bond between the clay minerals and results in exfoliation of clay blocks into colloidal-size fines . The surface charge, pH, and clay composition are factors that control clay dispersion. Dispersed smectite clays have variable shapes, for example, the swelling clay Na + -montmorillonite disperses into individual sheet-like layers while the nonswelling kaolinite readily disperses in the presence of water or noninhibiting drilling mud , to form a colloidal suspension. , Studies have shown that bacterial action can change the surface area, cation exchange capacity, and the layer charge on clays which can impact dispersion. Flocculation or aggregation, The addition of polymer macromolecules can destabilize the colloidal dispersion and cause the particles to aggregate and come out of suspension either by bridging the particles (attaching to the surface of two individual particles) or by neutralizing the surface charge on the particle .…”
Section: Water Chemistry and Shale Reactivitymentioning
confidence: 99%
“…It is always a worldwide challenge for well drilling in shale formations due to the wellbore instability problems induced by the interaction between shale and aqueous filtration including tight hole, sloughing, washout, caving and so on (Al-arfaj et al, 2014;Stelger and Leung, 1998). Oil-based drilling fluids are the first choice for most shale formations because of the outstanding shale stability, however, the drawback of high cost and stringent environmental legislation make them a much less attractive alternative than before (He et al, 2014;Stamatakis et al, 1995;Suter et al, 2011).…”
Section: Introductionmentioning
confidence: 99%